2007
DOI: 10.1017/s0007114507657936
|View full text |Cite
|
Sign up to set email alerts
|

Central adiposity in Brazilian schoolchildren aged 7–10 years

Abstract: Waist circumference (WC) is a measure of central adiposity related to elevated risk factor levels in children and adolescents. The aim of the present study was to describe WC percentiles in 7-to 10-year-old Brazilian children and to compare frequencies of obesity and overweight as defined by BMI and frequencies of excess and at risk of abdominal adiposity as defined by WC to the corresponding age and sex data from British references. A representative sample of 2919 schoolchildren of the city of Florianopolis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
1
16
0
5
Order By: Relevance
“…A prevalência de obesidade central foi de 4,9% (IC95%=4,3;5,5), sendo mais elevada nos meninos (5,9%;IC95%=4,9;6,8)…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A prevalência de obesidade central foi de 4,9% (IC95%=4,3;5,5), sendo mais elevada nos meninos (5,9%;IC95%=4,9;6,8)…”
Section: Resultsunclassified
“…In Maceió (AL) a study that used the same classification used herein found a central obesity prevalence of 9.3% in schoolchildren aged 7 to 17 years, but the study used a smaller cut-off point 30 . Higher prevalences were found in Florianópolis (SC) (10.4% in girls and 13.1% in boys) in children aged 7 to 10 years by a study that used British references for the classification 9 . The different prevalences are explained by the distinct age groups, methods, and cut-off points used for diagnosing central obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly higher waist circumference level in boys and significantly higher fasting insulin and HOMA-IR levels in girls indicated that abdominal obesity in males and insulin resistance in females were prevalent in children who were at elementary school level, which has also been shown in other studies. [15][16][17][18] The approach used in the present study had limitations. The present study included a larger percentage of boys than girls.…”
Section: Discussionmentioning
confidence: 99%
“…O perímetro de cintura aumentado durante a adolescência tem sido associado ao aumento do risco para DCV na vida adulta 12,13 . Percentis e/ou curvas de referência para o PC foram estimados para adolescentes em diversos países [11][12][13][14] , entre eles o Brasil 15 . Entretanto, os métodos de mensuração do PC 16 e de estimação dos percentis não foram iguais em todos os estudos, o que dificulta a definição de um ponto de corte universal de PC para predição de risco em saúde para adolescentes.…”
Section: N T R O D U ç ã Ounclassified